Postgraduate studies in Latin America – a look to the future - Giordani da Silva, Carolina; Nolli Bittencourtt, Marina (Revista Cuidarte, 2023)
Science is concerned with causality, seeking to understand reality through observation, verification, and experience. In this sense, hypothesis testing, and experimentation are considered scientific methods. Philosophy is concerned with the purpose of human life, the nature of being and reality, theory, and the limits of knowledge, using intuition, introspection, and reasoning as examples of philosophical methodologies. Science and philosophy share the same objective, which is to increase knowledge. Thus, the science of any discipline is linked to its philosophy, which provides the basis for understanding and developing theories for science. How to cite this article: Silva, Carolina Giordani; Bittencourtt, Marina Nolli. Pós-graduação na américa latina – um olhar para o futuro. Revista Cuidarte. 2023;14(1):e3141. http://dx.doi.org/10.15649/cuidarte.3141